2017
DOI: 10.2214/ajr.16.16434
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Subtalar Joint Motion With 4D CT: Proof of Concept With Cadaveric and Healthy Subject Evaluation

Abstract: Quantitative dynamic CT of the subtalar joint can provide a detailed analysis of joint motion, supporting its potential role in the evaluation of subtalar instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…To date, there is no literature relating to the assessment of the syndesmotic ligaments using novel CT technologies such as weight‐bearing cone beam CT of the lower extremity or 4D CT. Weight‐bearing cone beam CT could potentially be used for diagnosis of high grade injuries and may offer further dynamic information relating to the tibiofibular relationship that could potentially assist with management . 4D CT generates functional imaging of the joint and given its early promise in other articulations may have additional benefits in terms of being able to quantify the degree of instability in the syndesmosis …”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no literature relating to the assessment of the syndesmotic ligaments using novel CT technologies such as weight‐bearing cone beam CT of the lower extremity or 4D CT. Weight‐bearing cone beam CT could potentially be used for diagnosis of high grade injuries and may offer further dynamic information relating to the tibiofibular relationship that could potentially assist with management . 4D CT generates functional imaging of the joint and given its early promise in other articulations may have additional benefits in terms of being able to quantify the degree of instability in the syndesmosis …”
Section: Resultsmentioning
confidence: 99%
“…The dynamic evaluation of joint kinematics makes it possible to evaluate motion trajectory and patterns, and therefore could lead to identifying pathologies which may occur only during motion. The potential feasibility of 4DCT for such purposes is already shown in several studies 810 . Studies attempting to simulate pathological conditions showed that 4DCT may be able to detect altered joint kinematics.…”
Section: Introductionmentioning
confidence: 83%
“…Studies attempting to simulate pathological conditions showed that 4DCT may be able to detect altered joint kinematics. Simulation of subtalar joint instability by means of subsequent sectioning of the cervical ligament and the interosseous talocalcaneal ligament showed increases in joint motion amplitude 8 . In a similar study where the scapholunate ligament was cut to mimic scapholunate instability, orthopaedic surgeons could discern images before and after induced ligamentous damage.…”
Section: Introductionmentioning
confidence: 98%
“…Coronal tomosynthesis stress imaging provides clearer visualization of the subtalar joint compared with other cross-sectional imaging, such as CT or MRI, with lower dose of exposure to radiation and shorter examination time than those of CT. 172 Quantitative dynamic CT provides a detailed analysis of subtalar motion and can assist in the evaluation of subtalar instability. 53 …”
Section: Diagnosis Of Subtalar Instabilitymentioning
confidence: 99%